Is the international business environment the actual context for international business research? - Ferreira, Manuel Portugal (2009)
The International Business Environment (IBE) has been argued to be the essential context for international business (IB) studies and the distinguishing factor from other management studies and studies of large enterprises. Two content analysis show that many papers published in top tier IB journals either lack reference to any dimension of the IBE or tend to be uni-or bi-dimensional when addressing the IBE; it is not a surprise that the cultural dimension is the most often used. We suggest that: (a) there is need to developed more uni and multi-dimensional environmental constructs; (b) a more holistic view of the IBE provides richer insights on the actual complexity underlying IB research. Future studies that provide more comprehensive models of the IBE that overcome the usual broad classifications of the international environment as undefined and uncontrollable factors are warranted to advance conceptual and empirical research.